A system dynamics modelling of entrepreneurship and growth within firms - Lu, Jinfeng; Dimov, Dimo (Journal of Business Venturing, 2023)
This paper uses system dynamics modelling to explore processes through which entrepreneurial initiatives within firms lead to firm growth. Our model captures the interplay among various sub-processes and finds these processes form a complex system involving multiple interacting feedback processes. Simulation analysis shows that minor changes in firm conditions could lead to qualitatively different growth trajectories. They involve growth dynamics such as better before worse and worse before better scenarios. These findings prompt us to move beyond linear understanding of how entrepreneurship contributes to firm growth.